2010
DOI: 10.1128/aem.01707-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DysI, the Immunity Factor of the Streptococcal Bacteriocin Dysgalacticin

Abstract: DysI is identified as the protein that confers specific immunity to dysgalacticin, a plasmid-encoded streptococcal bacteriocin. dysI is transcribed as part of the copG-repB-dysI replication-associated operon. DysI appears to function at the membrane level to prevent the inhibitory effects of dysgalacticin on glucose transport, membrane integrity, and intracellular ATP content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…We believe that this is the first described case of co-transcription of genes involved in plasmid replication and a gene encoding a protein involved in the synthesis of EPS. However, this is not the first case in the literature of co-transcription of replication genes together with other genes, since the plasmidic dysI gene (encoding the immunity factor of the streptococcal bacteriocin dysgalacticin) is transcribed as part of the copG - repB - dysI replication-associated operon (Swe et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this is the first described case of co-transcription of genes involved in plasmid replication and a gene encoding a protein involved in the synthesis of EPS. However, this is not the first case in the literature of co-transcription of replication genes together with other genes, since the plasmidic dysI gene (encoding the immunity factor of the streptococcal bacteriocin dysgalacticin) is transcribed as part of the copG - repB - dysI replication-associated operon (Swe et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…equisimilis strain W2580, binds to membrane-bound glucose and/or the mannose phosphotransferase system (man-PTS). Once dysgalacticin has docked to the man-PTS it disrupts the cytoplasmic membrane by causing an efflux of potassium ions (K + ), which dissipates the membrane potential as seen in Streptococcus pyogenes [65]. Lactococcin A and B and some Listeria-active pediocin-like bacteriocins similarly bind man-PTS [66].…”
Section: Page 12 Of 40mentioning
confidence: 98%
“…Regarding bacteriocin produced by SDSE, Heng et al reported that dysgalacticin (DysA, UniProtKB - Q14DY1), a plasmid-encoded streptococcal bacteriocin, inhibits glucose transport [28]. DysI, the immunity factor of the streptococcal bacteriocin, suppresses the inhibitory effects of DysA [29]. However, neither dysA nor dysI were found in the three GA-SDSE strains or GG-SDSE strain ATCC 12394.…”
Section: Discussionmentioning
confidence: 99%